Cytotoxicity of cellulose fiber from coconut coir as a novelty base candidate on dental materials: Study experimental - cevanti, Twi agnita; Soesilo, Diana; Pangabdian, Fani; Wijaya, Yongki Hadinata; Puspita, Sinta; Hollanda, Ghita Hadi (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Fiber-reinforced composite (FRC) technology is being developed as an innovative material in dentistry. The depletion of fossil resources is a critical issue for current fiber composite resins. Cocos nucifera L. coconut fiber (coir) has high potential to replace synthetic fiber reinforcement as a new material to be developed. The aim of the study was to determine the toxicity of coir cellulose fiber composites as a base material. Methods: This was a post-test only control group experimental study. Cellulose from coir was synthesized using organosolvent, bleached with peroxide in alkaline solution, and nucleated with absolute ethanol. GT1 fibroblast cell viability test was conducted for cellulose fibers and then coir cellulose composites were made with a weight fraction of 70% cellulose fiber filler, and 30% BisGMA, TEGDMA and DGEBA matrix. Furthermore, cellulose coir composites were tested for toxicity from the results of composite immersion in artificial saliva for 7, 14, and 21 days using BHK-21 fibroblast cells. Results: The results of the Post Hoc LSD test concluded that the P-21 group had a significant difference between the K.Sel, P-7, P-14 treatment groups with a value of p<0.05.The safest dose of coir cellulose fiber is 12.5mg/ml; the results of the Kruskal-wallis test of the composite soaking time have significant differences between groups with a significance value of p<0.05 (p=0.001). Conclusion: Coir cellulose fiber is non-toxic so it can be a composite filler as one of the prerequisites to be a novelty base candidate in dental composite materials.KEY WORDS: coir, composite, toxicity, dental baseSitotoksisitas komposit serat selulosa sabut kelapa sebagai kandidat novelty basis pada material kedokteran gigi: Studi eksperimentalABSTRAKPendahuluan: Teknologi Fiber-reinforced composite (FRC) sedang dikembangkan sebagai bahan inovatif dalam kedokteran gigi. Menipisnya sumber daya fosil merupakan masalah kritis untuk resin komposit serat saat ini. Sabut kelapa Cocos nucifera L.(coir) memiliki potensi tinggi untuk menggantikan bahan penguat serat sintetis sebagai bahan baru yang akan dikembangkan. Tujuan penelitian mengetahui toksisitas komposit serat selulosa coir sebagai material basis. Metode: Jenis penelitian eksperimental post-test only control group. Selulosa dari coir disintesis menggunakan organosolvent, di bleaching dengan peroxide dalam larutan alkali, serta di nukleasi dengan etanol absolut. Dilakukan uji viabilitas sel fibroblas GT1 untuk serat selulosa kemudian pembuatan komposit selulosa coir dengan fraksi berat 70% filler serat selulosa, dan 30% matriks BisGMA, TEGDMA dan DGEBA. Selanjutnya komposit selulosa coir dilakukan uji toksisitas dari hasil rendaman komposit pada saliva buatan selama 7,14, dan 21 hari menggunakan sel fibroblas BHK-21. Hasil: Hasil uji Post Hoc LSD memberikan kesimpulan bahwa kelompok P-21 didapatkan perbedaan yang signifikan antara kelompok perlakuan K.Sel, P-7, P-14 dengan nilai p<0,05. Dosis paling aman serat selulosa coir sebesar 12,5mg/ml; hasil uji Kruskal-wallis dari lama perendaman komposit terdapat perbedaan yang bermakna antar kelompok dengan nilai signifikansi p<0,05 (p=0,001). Simpulan: Serat selulosa coir tidak toksik sehingga dapat menjadi filler komposit sebagai salah satu prasyarat untuk menjadi kandidat novelty basis pada material komposit kedokteran gigi.KATA KUNCI: coir, komposit, toksistas, basis kedokteran gigi